2014
DOI: 10.1002/anie.201409635
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Framework Aluminum Lewis Sites and Perturbed Aluminum Atoms in Zeolites as Determined by 27Al{1H} REDOR (3Q) MAS NMR Spectroscopy and DFT/Molecular Mechanics

Abstract: Zeolites are highly important heterogeneous catalysts. Besides Brønsted SiOHAl acid sites, also framework AlFR Lewis acid sites are often found in their H-forms. The formation of AlFR Lewis sites in zeolites is a key issue regarding their selectivity in acid-catalyzed reactions. The local structures of AlFR Lewis sites in dehydrated zeolites and their precursors--"perturbed" AlFR atoms in hydrated zeolites--were studied by high-resolution MAS NMR and FTIR spectroscopy and DFT/MM calculations. Perturbed framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 21 publications
7
79
0
Order By: Relevance
“…By comparing the TEM images of nanosheet MFI zeolites with different Si/Al molar ratios, it can be found that Al content plays a key role in the appearance of NMZ-X. Generally, a Si-O-Al structure is not as stable as a Si-O-Si structure in the MFI framework [42]. It is not easy to grow large area MFI nanosheets with low Si/Al molar ratio, because of the existence of abundant unstable Si-O-Al units.…”
Section: Characterization Resultsmentioning
confidence: 98%
“…By comparing the TEM images of nanosheet MFI zeolites with different Si/Al molar ratios, it can be found that Al content plays a key role in the appearance of NMZ-X. Generally, a Si-O-Al structure is not as stable as a Si-O-Si structure in the MFI framework [42]. It is not easy to grow large area MFI nanosheets with low Si/Al molar ratio, because of the existence of abundant unstable Si-O-Al units.…”
Section: Characterization Resultsmentioning
confidence: 98%
“…11,22,32 A recent report has shown that the perturbed aluminum species was attributed to terminal Al-OH in the hydrated zeolites, which was considered to be derived from hydrous tricoordination of the Al species. 33 However, most of these measurements were performed under hydration conditions. In the case of non-hydrated zeolites, it is difficult to distinguish FAL species owing to the resolution/sensitivity issues from the quadrupolar nature of the 27 Al isotope.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, reducing the number of neighboring oxygen groups bound to FAL yields a dramatic distortion of its local environment, and the extreme asymmetry of its surrounding electric eld results in a considerable line broadening of its 27 Al NMR resonance (usually with C Q > 30 MHz). 33,40 Therefore, the direct observation of tri-coordinated FAL species in a dehydrated sample is generally impossible using conventional 27 Al MAS NMR owing to its huge quadrupolar broadening and relatively low concentration, and tri-coordinated FAL was suggested to be the "NMR-invisible" species in zeolites. 26,33 Aer rehydration, the tri-coordinated FAL could be easily transformed into a symmetric tetra-coordinated FAL, 33,38 which is usually indistinguishable from the FAL of BAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This is first of all due to the limited number of zeolites with more or less known location of aluminum atoms. 5,[9][10][11][12][13][14][15][16][17] Then, even once the location is known, it is generally not unique so that identifying the precise location of the most stable intermediates and transition states is not straightforward. This is however a condition for the design of better catalysts.…”
Section: Introductionmentioning
confidence: 99%